Persiapan Industri Indonesia Menghadapi Pasar Dunia - Siti Nur Amalia; Muhammad Yasin (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Indonesia has entered the era of the fourth industrial revolution. This happens with technology as a basis for human life. Everything has become limitless and limitless due to the development of digital technology. Indonesia needs several regulatory and authority improvements to be able to face the world market. The aim of this research is to find out what Indonesian industry can do to face the world market, the impact that the presence of the industrial revolution 4.0 has, and the strategies that Indonesia can prepare and carry out in facing the World Market revolution. The object of this research is industry in Indonesia to face the world market. The method used for this research is a qualitative descriptive method, data is obtained from facts about the research subject by trying to reveal it thoroughly according to the context. The results of this research are (1) Creating jobs to increase people's income, increasing people's economic programs, increasing Turnover and Digitalization of People's Markets, building/revitalizing people's markets, establishing relationships between digital markets abroad (2) The most visible impact is in terms of available work (3) Make improvements to the flow of materials and goods, improve the quality of human resources, use digital technology, harmonize rules and policies. Bukit, M. (2014). Strategi dan inovasi pendidikan kejuruan darikompetensi ke kompetisi. Bandung: Alfabeta. Cognizant. Informed Manufacturing: The Next Industrial Revolution. http://www.cognizant.com/ InsightsWhitepapers/Informed-Manufacturing-TheNext-IndustrialRevolution.pdf. Davis, N. 5 ways of understanding the Fourth Industrial Revolution. November 16, 2015. http://www.weforum.org/ agenda/2015/11/5-ways-of-understanding-thefourth-industrialrevolution. Economist Intelligence Unit. From transplants to implants. December 11, 2015. http://www.eiuperspectives.economist.com/healthcare/transplants-implants. Edmon, A., & Oluiyi, A. (2014). Re-engineering technical vocationaeducation and training toward safety practice skill needs ofsawmill workers against workplace hazards in Nigeria [Versielektronik]. Journal of Education and Practice, 5 (7), 150-157. Era Revolusi Industri 4.0: Perlu Persiapkan Literasi Data, Teknologi dan Sumber Daya Manusia. (2018). Diambil 29 Desember 2023 dari http://belmawa.ristekdikti. go.id/2018/01/17/ era-revolusiindustri-4-0-perlu-persiapkan-literasi-data-teknologi-dan-sumber-daya-manusia/ Fakta ketergantungan pada teknologi (2014). Diambil 29 Desember 2023 dari http://www.beritasatu.com/gaya-hidup/232713-8-fakta-ketergantungan-pada-teknologi.html Hermann, M., Pentek, T., & Otto, B. (2016). Design Principles forIndustrie 4.0 Scenarios. Presented at the 49th HawaiianInternational Conference on Systems Science. Irianto, D. (2017). Industry 4.0; The Challenges of Tomorrow.Disampaikan pada Seminar Nasional Teknik Industri, Batu-Malang. Kagermann, H., Wahlster, W., & Helbig, J.(2013). Recommendations forImplementing the Strategic Initiative Industrie 4.0. Industrie 4.0Working Group, Germany. Hitt, Mihael.A , Ireland, R. Duane, Robert E, Hoskinsson. 2001. Strategic Management Competitiveness and Globalization Concepts Thomson learning Asia, Singapore. Hamel Gary, Prahalad C.K. Competing For The Future. 1994. Harvard Business School Press Boston, Massachusetts. "Making Indonesia 4.0, Fokus 5 Industri Apa Saja.", https://economy.okezone.com/ read/2018/04/04/320/1881885/ making-indonesia-4-0-fokuspengembangan-5-industri-apasaja, diakses 29 Desember 2023. "Making Indonesia 4.0: Strategi RI Masuki Revolusi Industri K-4.", http://www.kemenperin. go.id/artikel/18967/ MakingIndonesia-4.0:-Strategi-RIMasuki-Revolusi-Industri-Ke-4, diakses 3 Mei 2018. “Menuju Revolusi Industri 4.0 Jokowi Diminta Bentuk Badan Riset Nasional”, Kompas, 29 April 2018, hal 3. "Pemerintah Luncurkan Making 3932.", https://ekon.go.id/ 23 Hak cipta dilindungi oleh undang-undang. Dilarang mengutip atau memperbanyak sebagian atau seluruh isi tulisan ini tanpa izin penerbit. Info Singkat © 2009, Pusat Penelitian Badan Keahlian DPR RI http://puslit.dpr.go.id ISSN 2088-2351 berita/view/pemerintahluncurkan-making.3932.html, diakses 29 Desember 2023. “Pemerintah RI dan Ceko sepakat tingkatkan Investasi Industri Dua Kali Lipat”, Tribun Bisnis, 29 Desember 2023 hal 8. "Revolusi Industri 4.0", http://id.beritasatu.com/home/ revolusi-industri-40/145390, diakses 29 Desember 2023. "Revolusi 4.0, Catatan Dari ISSA ICT 2018", http://id.beritasatu.com/ home/revolusi-40- catatan-dariissa-ict-2018/174772, diakses 8 Mei 2018. "Strategi Hadapi Dampak Industri 4.0", http://id.beritasatu.com/ home/strategi-hadapi- dampakrevolusi-industri-40/174260, diakses 2 Mei 2018.